Digital Economy Taxation and Global Tax Governance: Legal Challenges and Future Directions - Hadiyanto, Indrawan; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pekalongan, 2024)
The rise of the digital economy has posed fundamental challenges to traditional tax principles and global tax governance. In response, the OECD/G20 Inclusive Framework has proposed a Two-Pillar Solution – comprising a new profit allocation mechanism and a global minimum tax – to modernise corporate taxation for the digital era. However, these reforms encounter substantial legal obstacles, including jurisdictional conflicts, potential overlaps with national digital service taxes, and debates over treaty reform and tax sovereignty. This article examines these complexities through doctrinal and comparative analysis of international tax laws, OECD models, and UN proposals. The analysis explores how rules on permanent establishment, profit allocation and anti-abuse respond to digitalisation, and how the Inclusive Framework negotiations affect global tax governance. Tensions between unilateral measures (such as digital services taxes) and multilateral solutions are considered, as well as equity concerns of developing countries. The findings highlight key challenges: the difficulty of reconciling national tax sovereignty with collective agreements, the risk of double taxation or gaps, and the contested roles of the OECD versus the United Nations in shaping future norms. The study concludes that coherent global tax governance will require both legal innovation and strengthened cooperation. It suggests future directions, including refining treaty rules and broadening international consensus (potentially beyond the OECD-led forum), to achieve fair and effective taxation in the digital age.